2013
DOI: 10.1039/c3cc44317e
|View full text |Cite
|
Sign up to set email alerts
|

n→π* interactions in poly(lactic acid) suggest a role in protein folding

Abstract: Poly(lactic acid) (PLA) is a versatile synthetic polyester. We noted that this depsipeptide analog of polyalanine has a helical structure that resembles a polyproline II helix. Using natural bond orbital analysis, we find that n→π* interactions between sequential ester carbonyl groups contribute 0.44 kcal/mol per monomer to the conformational stability of PLA helices. We conclude that analogous n→π* interactions could direct the folding of a polypeptide chain into a polyproline II helix prior to the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 39 publications
0
55
0
Order By: Relevance
“…Consider poly(lactic acid) (PLA), a biodegradable polyester (Figure 8A). 26 Fiber diffraction has shown that the backbone dihedral angles in PLA resemble those of the PPII helix of peptides, which takes advantage of numerous n →π* interactions (vide supra). Computation placed the average energy of an n →π* interaction in PLA at 0.44 kcal/mol, and analysis of small-molecule crystal structures demonstrated characteristic pyramidalization of the acceptor carbonyl group that results from accepting an n →π* interaction.…”
Section: Contributions To Other Polymersmentioning
confidence: 99%
“…Consider poly(lactic acid) (PLA), a biodegradable polyester (Figure 8A). 26 Fiber diffraction has shown that the backbone dihedral angles in PLA resemble those of the PPII helix of peptides, which takes advantage of numerous n →π* interactions (vide supra). Computation placed the average energy of an n →π* interaction in PLA at 0.44 kcal/mol, and analysis of small-molecule crystal structures demonstrated characteristic pyramidalization of the acceptor carbonyl group that results from accepting an n →π* interaction.…”
Section: Contributions To Other Polymersmentioning
confidence: 99%
“…[38][39][40] Their further role in protein structure, folding and stability can be well anticipated. 37,[41][42][43] There are numerous reports on hydrogen bonded carbonyl complexes by theoreticians and experimentalists [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] in the past and even today. [62][63][64][65][66][67][68] For example, the earlier work by Bobadova-Parvanova and his co-worker investigated the hydrogen bonded complexes between open-chain substituted aliphatic carbonyl compounds and hydrogen fluoride at the HF/6-31G * * level.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations studies conducted on some synthetic polymers (e.g. m-terphenyl-based π-conjugated polymer [6], poly(ethylene glycol) (PEG) [7], poly(ethylene imine) (PEI) [8], squaraine polymers [9]) shown their tendency to form helixes.…”
Section: Introductionmentioning
confidence: 99%